Health impact assessment of road traffic noise exposure based on different densification scenarios in Malmö, Sweden. (April 2023) - Flanagan, Erin; Malmqvist, Ebba; Oudin, Anna; Sunde Persson, Karin; Alkan Ohlsson, Johanna; Mattisson, Kristoffer
Highlights: Health impact assessments of road traffic noise exposure are presented for two alternative densification scenarios. It is possible to considerably reduce noise exposure with a more health-centred densification strategy. A more health-centred strategy could help prevent annoyance and adverse sleep disturbance. A more health-centred strategy could help prevent incidence and mortality of ischemic heart disease. Urban planning initiatives must be more ambitious in order to create healthy, sustainable cities. Abstract: While urbanization provides many opportunities to those arriving in thriving urban areas, a greater number of residents necessitates the expansion of housing and infrastructure. This is often achieved through densification, which can lead to increased noise, particularly through increased road traffic. A key challenge of promoting healthy urban planning is to understand potential health effects, especially on the local level. The aim of the present study is, therefore, to estimate and compare the health impacts of road traffic noise exposure for various urban densification scenarios within a neighborhood (Lorensborg) in Malmö, Sweden. The three scenarios include 1) Present-day, representing the study area as it is presently organized; 2) Planned municipal strategy (the city of Malmö's own densification plans) and 3) Health-centred, which involves major structural alterations and reflects an effort prioritize a health-centred approach. Noise was modelled using the Nordic prediction method for road traffic. Health outcomes included noise annoyance, adverse sleep disturbance, ischemic heart disease (IHD) incidence and mortality. Within all scenarios, a large proportion of the study population was exposed above the WHO's health-based guideline value (Lden 53 dB): >80% for Present-day and Planned municipal strategy scenarios, and almost 50% in the Health-centred scenario. Still, densifying Lorensborg (population ≈9, 600) according to the Health-centred scenario could prevent 549 cases of highly annoyed, 193 cases of adverse sleep disturbance, 4.7 new cases of IHD (8.9% of total cases), and 1.5 deaths due to IHD (17.8% of IHD mortality) annually. The results demonstrated that it is possible to considerably lower the health impact with a more health-centred densification strategy. Important co-benefits for public and environmental health include air pollution reduction and green space creation, although their health effects were not quantified in the present study. Urban planning initiatives must be more ambitious in order to create healthy, sustainable cities.